Le rôle du langage ordinaire dans la subversion du droit, un défi pour l’épistémologie juridique : analyse de processus de renversement et de resignification du droit du mariage (1960-2013) - Elena Mascarenhas (Criminocorpus, 2025)
This article explains the mechanisms by which ordinary language subverts positive law in a case study devoted to marriage law between the 1960s and 2013. By comparing the evolution of norms with that of the the vocabulary of unions, it identifies two subversive processes: renversement and resignification. This juridical study feeds its approach with analytical philosophy (Austin) and social philosophy (Wittig, Butler, Haslanger), which enables it to refine the theoretical understanding of the discursive subversion of law and tends to challenge the boundaries of juridicity. At a time when legal language is defined as a specialised language in the image of the law, the legal sciences are invited to think of ordinary language as a source of knowledge about the law, and to draw the consequences for legal epistemology.